Early modern mining in Southwest China and Highland Southeast Asia [data]: collection of material and analyses on sites of silver exploitation, field materials and research papers on metal mining - Kim, Nanny (Universität, 2023)
Material and analyses on sites of historic silver mining and research papers of the DFG research projects Mining and metallurgy in Southwest China, 14th to 19th centuries” and “Environments, people and mining in the Far Southwest of China since 1500: Cross-disciplinary explorations” / Dokumentationen historischer Bergbaustandorte und Papers aus den DFG-Projekten "Bergbau und Metallurgie in Südwestchina, 14. bis 19 Jahrhundert: Archäo-metallurgische und historisch geographische Untersuchungen" und Umwelt, Gesellschaft und Bergbau im fernen Südwestens Chinas seit 1500”